Regulating zombie mortgages - Jonathan Lee; Duc Duy Nguyen; Huyen Nguyen (Halle Institute for Economic Research (IWH), 2024)
Using the adoption of Zombie Property Law (ZL) across several US states, we show that increased lender accountability in the foreclosure process affects mortgage lending decisions and standards. Difference-in-differences estimations using a state border design show that ZL incentivizes lenders to screen mortgage applications more carefully: they deny more applications and impose higher interest rates on originated loans, especially risky loans. In turn, these loans exhibit higher ex-post performance. ZL also affects lender behavior after borrowers become distressed, causing them to strategically keep delinquent mortgages alive. Our findings inform the debate on policy responses to foreclosure crises.
urn:nbn:de:gbv:3:2-1065469
Keywords: G21; G28; K25; 330; Zombie lending; mortgage screening; mortgage renegotiation